The Construction of The Identity of Islamic Youth Movement Cadres in The March 'Pemuda Pembela Agama' By Suraedi: a Semiotic Analysis of Roland Barthes - Thaifur Rayya Difadrana; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
The purpose of this study is to reveal the construction of the identity of Pemuda Persis cadres as embodied in the song Mars Pemuda Pembela Agama by Suraedi through the semiotic theory of Roland Barthes. This research employs a descriptive qualitative method with a semiotic theoretical approach based on Roland Barthes' framework. This approach is chosen to uncover the symbolic meanings within the lyrics of Pemuda Pembela Agama as a representation of the ideological identity of Pemuda Persis cadres. The data analysis technique follows Barthes’ semiotic model, which includes denotative analysis to uncover the literal meaning of the lyrics, connotative analysis to interpret meaning based on the cultural and ideological context of the organization, and myth analysis to explore how the ideological message is naturally accepted by the organization’s members. The song Pemuda Pembela Agama by Suraedi represents the identity of Pemuda Persis cadres through Barthes’ semiotic approach, from literal to ideological meaning. Its lyrics emphasize the role of youth as pioneers of Islamic preaching (dakwah) and social transformation with intellectual strength grounded in the Qur'an and Hadith. Through connotation and myth, the cadres are portrayed as guardians of Islamic purity, reformers, and intellectual fortresses of the Muslim community. This song is not merely a formal symbol but serves as an ideological instrument to shape cadres with religious, intellectual, militant, and socially driven character.